Iglesia, catolicismo popular y Estado: fundamentos socio-históricos de un pueblo michoacano (Tzintzun, Revista de Estudios Históricos, 2016)
During the institutionalization period of the government originating in theMexican Revolution, certain social and politican projects were encouragedwhich aimed at renewing national society in its broadest sense. In rural areas,the most important of these projects was to provide people with land. As aresult of this state project, a social identity and rural politics started to emerge.his process, known as agrarism, faced both wide acceptance and hardresistance among the population. his paper analyzes and collects historicalfacts of key importance in the village of Tiríndaro, Michoacán state, whichshow the diferent phases of the arrival and consolidation of the new agrarianstate project at the beginning of the 20th century. It will also shed light onhow disruptive it proved to be in a village which had earlier been characterizedby its industriousness and devoted catholicism. hus, starting out fromthe idea that the state and the church are contingent societies, this researchpaper sets the premise that the society of Tiríndaro is a product of social, politicaland cultural parameters coming from the Catholic church, the nationalState and recent actions of a popular catholicism.
Keywords: state; church; popular catholicism; Michoacán; agrarism